Marine Oil Spillage in Malaysian Waters - Ngien, S. K.; Gisen, J. I. A. (Penerbit Universiti Malaysia Pahang, 2018)
Oil spill is defined as the release of liquid petroleum hydrocarbon into the environment due to anthropogenic activities (Najafi et al., 2009). Oil spills in general, whether on land or in natural water bodies, constitutes some of the worst environmental disasters known to man. However, oil spills in the marine environment are particularly destructive to nature and disruptive to humans, especially when the extent of the spillage intrudes into all three of the ‘spheres’ that make up the marine environment; the hydrosphere, biosphere and the lithosphere.